Analisis Budaya Kerja Karyawan PT. Indonesia Thai Summit Auto - Bayu Firi Rizaldhi; Uus Md Fadli (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This article discusses the analysis of employee work culture at PT ITSA, a leading information technology company. A strong and positive work culture is an important factor in the company's success. The purpose of this study is to understand the work culture that exists at PT ITSA, identify strengths, weaknesses, and potentials that can be improved. This research also looks at the shift in values in the work environment which is influenced by the new generation of employees. The research method used is qualitative analysis involving interviews with employees and observations of work culture practices in the company. The results of this research are expected to provide valuable insights for PT ITSA in building a healthy, inclusive, and achievement-oriented work culture. In addition, this research can also be a guideline for other companies that want to manage their work culture well.